(untitled) (Experimental biology, 2009)
Researches 2006 - 2009 of population Hypophtnalmichthys molitrix in the Kapshagajsky water basin specify a stable condition. Meanwhile in population of a white Hypophtnalmichthys molitrix of 2009 occurrence advanced age groups with high fruitfulness is noted.